2006
DOI: 10.1111/j.1444-2906.2006.01218.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone-like substance in the rotifer Brachionus plicatilis

Abstract: A growth hormone (GH)-like substance was extracted from the rotifer Brachionus plicatilis and subsequently purified by gel filtration and ion exchange chromatography. The GH-like substance had a molecular weight of approximately 28 kDa and had cross-reactivity with salmon GH antibody. In vivo bioassay showed a higher intrinsic rate of increase and net reproduction rate of B. plicatilis treated with the GH-like substance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…In this regard, it is interesting to raise the antibody against the isolated protein in order to obtain other possible proteins having similar functions from CM. Gallardo et al (2006) isolated a growth hormonelike protein with a molecular weight of 25000 from the CE from the rotifer B. plicatilis NH3 strain. Furthermore, Snell et al (2006) isolated the steroidogenesis-inducing protein (SIP) with a molecular weight of 39000 from CM of the rotifer B. plicatilis RUS strain.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it is interesting to raise the antibody against the isolated protein in order to obtain other possible proteins having similar functions from CM. Gallardo et al (2006) isolated a growth hormonelike protein with a molecular weight of 25000 from the CE from the rotifer B. plicatilis NH3 strain. Furthermore, Snell et al (2006) isolated the steroidogenesis-inducing protein (SIP) with a molecular weight of 39000 from CM of the rotifer B. plicatilis RUS strain.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies about the effect of hormones on rotifers have been focused on the population and sexual reproduction parameters in an ecotoxicology paradigm. A few studies have suggested that vertebrate and invertebrate hormones, such as growth hormone, human chorionic gonadotropin, juvenile hormone and 17β-estradiol, affect asexual population growth and mictic reproduction in the rotifers Brachionus plicatilis and Brachionus calyciflorus (GALLARDO et al, 1997;PRESTON and SNELL, 2001;RADIX et al, 2002;GALLARDO et al, 2006). A receptor similar to the vertebrate progesterone receptor was discovered in the rotifer Brachionus manjavacas (SNELL and DESROSIERS, 2008;SMITH et al, 2010;STOUT et al, 2010).…”
Section: Introductionmentioning
confidence: 98%
“…Ominato et al identified an hGH-like protein in the pituitary of Petromyzon marinus in 2002 [8] . Gallardo et al found an hGH-like protein in rotifer using antibodies to the growth hormone of salmon, and demonstrated its function in promotion of rotifer reproduction [9] . Phares’s research group conducted a study on Spirometra mansonoides and found that the parasite secreted a protein that can bind to the hGH receptor [10] .…”
Section: Introductionmentioning
confidence: 99%